Sagittal Plane Correction Using Lateral Transpsoas Approach: Effect of Cage Angulation and Surgical Technique on Segmental Lordosis. Issue 1 (April 2016) - Yoon, S. Tim; Melikian, Rojeh; Kim, Jin Young; Park, Kun Young; Yoon, Caroline; Hutton, William
Introduction: Lordotic cage insertion through lateral transpsoas approach is being used increasingly for restoration of sagittal alignment. However, the degree of correction achieved by varying cage angle as well as ALL release and posterior element resection is not well defined. The objective of this study is to determine the degree of segmental correction which could be achieved through lateral transpsoas approach by varying cage angle as well as adding anterior longitudinal ligament (ALL) release and posterior element resection. Material and Methods: Thirteen human cadaveric lumbar motion segments between L1 and L5 were dissected into single motion segments. Segmental angles and disk heights were measured under both 50N and 500N loads under the following conditions: Intact specimen, discectomy (collapsed disk simulation), insertion of parallel cage, 10° cage, 30° cage with ALL release, 30° cage with ALL release and spinous process (SP) resection, 30° cage with ALL release, SP resection, facetectomy and compression with pedicle screws. Results: Segmental lordosis was not increased by with either parallel or 10° cages as compared with intact disks, and contributed small amounts of lordosis when compared with the collapsed disk condition. Placement of 30° cages with ALL release increased segmental lordosis by 10.5°. Adding SP resection increased lordosis to 12.39°. Facetectomy and compression with pedicle screws further increased gains in lordosis to 26.4° in the 50N group and 25.8° in the 500N group. Neither group experienced a decrease in either anterior or posterior disk height. Conclusion: Insertion of parallel or 10° cage has little effect on lordosis. 30° cage insertion and ALL release resulted in an increase of lordosis by 10.5°. The addition of SP resection and facetectomy allowed increases in correction of up to 26.4°. No interventions resulted in decrease in either anterior or posterior disk height suggesting gains were achieved without causing foraminal stenosis.